The Experience of Conflict Management of Public Secondary School Administrators: A Phenomenological Inquiry - Imperial, Joebel G.; Madrigal, Dennis V. (Technium Social Sciences Journal, 2021)
The school administrators’ skill in managing conflict and resolution is vital towards creating a peaceful and productive working environment. The purpose of this phenomenological study is to explore the lived experiences of public secondary school administrators on conflict management. Using a purposive sampling technique, three school administrators participated in an in-depth interview. The data were analyzed using the recursive textual analysis aided by the framework of Lichtman. The study’s findings show that school administrators primarily consider the source of conflict to understand the appropriate approach to apply. By classification, the conflict between teachers usually rooted in jealousy, faction, personal grudges, and pride. In contrast, conflicts between teachers and administrators would usually involve the performance of duties. Moreover, they believe that there is no single approach to be followed in the implementation of conflict resolution strategies since it depends on the situation and the parties involved. The findings suggest that each person is dynamic, and the beauty of dynamism of people enables them to understand and resolve conflicts in the end.